Porous material as well as preparation method and application thereof
By preparing a combination of copper-cerium coexisting metal-organic framework materials and fluorescent materials, the problem of rapid and highly sensitive monitoring of Kr-85 gas in nuclear facilities was solved, achieving selective adsorption and detection of Kr-85 gas, thus ensuring the safety of nuclear facilities and environmental protection.
Patent Information
- Application Number
- CN202511151679.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-15
- Publication Date
- 2025-11-25
AI Technical Summary
Existing technologies are insufficient for the rapid and highly sensitive monitoring and adsorption of radioactive krypton gas Kr-85 released from large nuclear facilities such as nuclear power plants and reprocessing plants, making it difficult to detect abnormal operating conditions of the facilities in a timely manner.
A porous material was prepared using a metal-organic framework containing copper ions (Cu2+) and cerium ions (Ce3+) and a 3,6-di-4-pyridyl-1,2,4,5-tetraazine organic ligand. This material was then combined with the fluorescent material 9,10-diphenylanthracene to achieve selective adsorption of Kr-85 gas and direct detection of β particles.
It enables rapid and highly sensitive measurement of Kr-85 gas, reduces the size and cost of the measurement system, supports the safe and stable operation of nuclear facilities, and ensures the safety of personnel and the environment.
Smart Images

Figure CN121005909A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of novel materials technology, specifically relating to a porous material, its preparation method, and its applications. Background Technology
[0002] During operation, large nuclear facilities such as nuclear power plants and reprocessing plants release large quantities of radioactive krypton gas, such as Kr-85, produced by nuclear fission into the environment. Kr-85 has a half-life of approximately 10.73 years and undergoes beta decay. Its short-term, large-scale release into the environment can pose a significant hazard to surrounding personnel and the environment. Therefore, rapid and highly sensitive monitoring of the Kr-85 activity concentration in the gaseous effluents of large nuclear facilities such as nuclear power plants and reprocessing plants can effectively monitor emissions and promptly detect abnormal operational conditions.
[0003] Therefore, there is a need for novel materials that can rapidly and sensitively detect and adsorb Kr-85. Summary of the Invention
[0004] The purpose of this invention is to provide a novel porous material that can be used as an adsorption and detection material for Kr-85 gas. Specifically, this material has both selective adsorption capabilities for Kr-85 gas and the ability to rapidly and sensitively detect the β particles emitted during its decay, thus having practical significance for achieving rapid and highly sensitive measurement of Kr-85.
[0005] To achieve the above objectives, the present invention provides a porous material, including a metal-organic framework material, wherein the metal-organic framework material includes metal ions and organic ligands;
[0006] The metal ion is copper ion (Cu). 2+ ) and cerium ions (Ce) 3+ The organic ligand is selected from 3,6-bis-4-pyridyl-1,2,4,5-tetraazine;
[0007] At least 80% of the micropores in the porous material have The aperture.
[0008] In some embodiments, the molar ratio of copper ions to cerium ions is 1 to 5.
[0009] In some embodiments, the BET specific surface area of the metal-organic framework material is 2185 m². 2 / g.
[0010] In some embodiments, the porous material further includes a fluorescent material, optionally selected from 9,10-diphenylanthracene.
[0011] The present invention also provides a method for preparing the above-mentioned porous material, comprising:
[0012] Step 1: Mix and dissolve hexafluorosilicic acid, copper hydroxide, and cerium hydroxide to obtain a first solution containing CuSiF6 and Ce2(SiF6)3;
[0013] Step 2: Slowly add the first solution dropwise into a solution containing 3,6-bis-4-pyridyl-1,2,4,5-tetraazine to obtain the second solution;
[0014] Step 3: Heat the second solution and continue stirring;
[0015] Step 4: Slowly add a mixed solution of thiol and methanol dropwise to the second solution while continuing to stir to obtain a suspension; and
[0016] Step 5: Filter the suspension, then wash the precipitate and dry it to obtain the metal-organic framework material.
[0017] In some embodiments, the method further includes:
[0018] Step 6: Immerse the metal-organic framework material in an organic solution of the fluorescent material.
[0019] In some embodiments, in step 1, the molar ratio of copper hydroxide to cerium hydroxide is 1 to 5.
[0020] In some embodiments, in step 3, the second solution is added to 30°C and the solution is continuously stirred for 12 hours.
[0021] In some embodiments, in step 4, the volume ratio of thiol to methanol is 0.1 to 1; and the volume ratio of the second solution to the mixed solution of thiol and methanol is in the range of 1:100 to 1:50.
[0022] In some embodiments, in step 5, the drying is carried out at 100°C under vacuum for 5 hours.
[0023] In some embodiments, in step 6, the organic solution of the fluorescent material is a methanol solution of 9,10-diphenylanthracene.
[0024] The present invention also provides the use of the above-mentioned porous material in the adsorption and detection of radioactive krypton gas.
[0025] The porous material synthesized through this invention overcomes the challenge of rapid and highly sensitive measurement of Kr-85 activity concentration in gaseous effluents from nuclear facilities, enabling effective monitoring of emissions and abnormal operating conditions of nuclear facilities, supporting the safe and stable operation of nuclear facilities, and ensuring the safety of personnel and the environment. Attached Figure Description
[0026] Figure 1 A flowchart of the method for preparing the porous material of the present invention is shown. Detailed Implementation
[0027] The following detailed description discusses exemplary embodiments. The specific embodiments included herein should not be construed as limiting the invention. Furthermore, while specific language may be used to describe features, actions, and / or structures in the embodiments described herein, the claims are not limited to the described features, actions, and / or structures. Those skilled in the art will understand that other embodiments, including improvements, are within the spirit and scope of the invention.
[0028] Throughout this specification, unless otherwise specified, the terminology used herein should be understood as having the meaning as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0029] Kr-85 is a β-γ emitter with a half-life of 10.73 years. If released into the atmosphere, it could be inhaled or cause external radiation exposure to humans. Currently, monitoring of Kr-85 in nuclear power plants and other nuclear facilities typically employs two methods: high-pressure cylinder sampling with gamma spectroscopy analysis and cryogenic sampling with liquid scintillation measurement. The high-pressure cylinder method has a relatively low detection limit (approximately 10 keV) for Kr-85 measurements due to the low branching ratio of the Kr-85 gamma characteristic peak (514 keV, 0.434%). 4 Bq / m 3 Low-temperature sampling liquid flash measurement method is difficult to achieve rapid measurement and response functions due to its long sampling time (sampling time > 3 hours).
[0030] Metal-organic frameworks (MOFs) are a novel type of coordination compound material. Compared with traditional porous adsorbents such as activated carbon and molecular sieves, they have advantages such as large specific surface area, diverse pore structure, tunable physicochemical properties, uniform pores, and easy modification and adjustment of pore structure. They have been widely used in research in catalysis, sensing, electronics and other fields.
[0031] In this application, by providing a pore size slightly larger than that of a krypton molecule... A porous material with a diameter of [diameter missing] was used to selectively adsorb krypton gas, thus successfully developing a novel material for adsorbing and detecting radioactive krypton gas. In other words, the porous material provided in this application has the ability to be optimized and controlled to [diameter missing]. The main micropore diameter in the region is slightly larger than that of krypton molecules. Diameter, suitable for selective adsorption of krypton.
[0032] In this application, "major micropores" means at least 80% of the total porosity, such as 85%, 90%, 95%, 96%, 97%, but not limited thereto.
[0033] In this application, the porous material is a metal-organic framework material, which includes metal ions and organic ligands, wherein the metal ions are copper ions (Cu ions). 2+ ) and cerium ions (Ce) 3+ The organic ligand is 3,6-bis-4-pyridyl-1,2,4,5-tetraazine. By selecting this specific organic ligand, a copper-cerium coexisting mixed metal MOF material can be formed. In this material, the copper-based metal-organic framework is mainly used for the physical adsorption of Kr-85 gas, while the cerium-based metal-organic framework contains Ce... 3+ Used for direct detection of β particles (Ce) emitted by KR-85. 3+ (By absorbing the energy of β particles to generate fluorescence), the porous material of this application can simultaneously adsorb and detect Kr-85.
[0034] In this application, the ratio of copper ions to cerium ions ranges from 1 to 5, such as 1, 2, 3, 4, and 5. Within this range, the porous material of this application can effectively perform adsorption and detection functions.
[0035] In this application, the BET specific surface area of the porous material is 2185 m². 2 / g. Porous materials with this specific surface area can achieve rapid and highly sensitive adsorption and detection.
[0036] In this application, the porous material further includes a fluorescent material. By incorporating the fluorescent material, it is possible to perform tests by measuring the amount of luminescence, thereby further improving the sensitivity of the material in measuring radioactive krypton.
[0037] In this application, the fluorescent material can be selected from 9,10-diphenylanthracene. 9,10-diphenylanthracene luminescent material has strong fluorescence properties, thereby significantly improving the fluorescence emission per unit volume of the fluorescence-enhanced porous adsorbent material.
[0038] This application also provides a method for preparing the above-mentioned porous material. In this method, hexafluorosilicic acid, copper hydroxide, and cerium hydroxide are first mixed and dissolved in a certain proportion to obtain a mixed aqueous solution of CuSiF6 and Ce2(SiF6)3. 3,6-di-4-pyridyl-1,2,4,5-tetraazine and thiol are dissolved in methanol solution to obtain a mixture of 3,6-di-4-pyridyl-1,2,4,5-tetraazine-methanol, thiol, and methanol. A certain volume of the CuSiF6 and Ce2(SiF6)3 mixed aqueous solution is slowly added dropwise to the 3,6-di-4-pyridyl-1,2,4,5-tetraazine-methanol solution (volume ratio 1:10), and the mixed solution is heated to 30°C in a water bath while continuously stirring for 12 hours. A certain volume of the thiol and methanol mixture is slowly added dropwise to the above-mentioned mixed solution in the water bath (volume ratio range 1:100-1:50), maintaining the water bath heating temperature at 30°C while continuously stirring the solution for 12 hours. The stirred suspension was filtered to obtain a precipitate sample, which was then washed with methanol to remove surface impurities. The washed precipitate was then vacuum dried at 100°C for 5 hours. After drying, helium gas was passed through for protection until the material cooled to room temperature, yielding a porous adsorbent powder.
[0039] During the above solution mixing process, the pyridine group, as a metal coordination site, reacts with CuSiF6 and Ce2(SiF6)3 to generate a mixed powder of copper-based and cerium-based metal-organic framework materials.
[0040] In the above preparation method, the addition of thiols is used to control the micropore size of the copper-based metal-organic framework material. By controlling the amount of thiol groups added within a certain range and introducing thiol groups to change the ligand length, the pore size of copper-based metal-organic framework material mixed powders can be precisely controlled to approximately [specific value missing]. The diameter of a krypton molecule is approximately Precisely regulated Copper-based metal-organic frameworks with large pore sizes can efficiently selectively adsorb krypton gas.
[0041] In other words, in this invention, to improve the measurement response time of radioactive krypton, trivalent cerium ion inorganic fluorescent luminescent material and 9,10-diphenylanthracene organic fluorescent luminescent material are added sequentially during the material synthesis process to enhance the material's sensitivity in measuring radioactive krypton. Testing shows that this material can dynamically adsorb trace amounts of radioactive Kr-85 gas at the ppm level at room temperature, with a dynamic adsorption capacity of 0.13 mmol / kg and a detection efficiency of approximately 28% for Kr-85 gas. This novel material can be applied to the rapid and highly sensitive monitoring of radioactive krypton in gaseous effluents from nuclear facilities, while significantly reducing the size and cost of radioactive krypton measurement systems.
[0042] The present invention will be described in more detail below through embodiments. It should be understood that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0043] Example 1
[0044] First, dissolve 3 moles of hexafluorosilicic acid, 1 mole of copper hydroxide, and 1 mole of cerium hydroxide in a mixture to obtain a mixed solution of CuSiF6 and Ce2(SiF6)3. Then, dissolve 20 g of 3,6-di-4-pyridyl-1,2,4,5-tetraazine and 20 mL of thiol separately in 300 mL of methanol to obtain a 3,6-di-4-pyridyl-1,2,4,5-tetraazine-methanol solution and a mixture of thiol and methanol.
[0045] First, slowly add 10 mL of a mixed solution of CuSiF6 and Ce2(SiF6)3 dropwise into 100 mL of a 3,6-bis(4-pyridyl)-1,2,4,5-tetraazine-methanol solution. Then, heat the mixed solution in a water bath to 30°C and stir continuously for 12 hours.
[0046] Slowly add 10 mL of the mixture of thiol and methanol dropwise into the above water bath solution, maintain the water bath temperature at 30°C and continuously stir the solution for 12 hours.
[0047] The stirred suspension was filtered to obtain a precipitate sample, which was then washed with methanol to remove surface impurities. The washed precipitate was then vacuum dried at 100°C for 5 hours. After drying, helium gas was passed through for protection until the material cooled to room temperature, yielding a porous adsorbent powder.
[0048] The obtained porous adsorbent material was tested using a combination of scanning electron microscopy and molecular probe methods, revealing that at least 80% of the micropores possess... The aperture.
[0049] Furthermore, the specific surface area of this porous material was measured to be 2185 m² using the BET method. 2 / g.
[0050] Example 2
[0051] First, dissolve 3 mol of hexafluorosilicic acid, 1 mol of copper hydroxide, and 1 mol of cerium hydroxide in a mixture to obtain a mixed aqueous solution of CuSiF6 and Ce2(SiF6)3. Then, dissolve 20 g of 3,6-bis-4-pyridinyl-1,2,4,5-tetraazine and 20 mL of thiol in 300 mL of methanol to obtain a 3,6-bis-4-pyridinyl-1,2,4,5-tetraazine-methanol solution and a mixture of thiol and methanol.
[0052] First, slowly add 10 mL of a mixed aqueous solution of CuSiF6 and Ce2(SiF6)3 dropwise into 100 mL of a 3,6-bis-4-pyridyl-1,2,4,5-tetraazine-methanol solution. Heat the mixed solution in a water bath to 30°C and stir continuously for 12 hours.
[0053] Slowly add 10 mL of the thiol and methanol mixture to the above water bath solution, maintain the water bath temperature at 30°C and continuously stir the solution for 12 hours.
[0054] The stirred suspension was filtered to obtain a precipitate sample, which was then washed with methanol to remove surface impurities. The washed precipitate was then vacuum dried at 100°C for 5 hours. After drying, helium gas was passed through for protection until the material cooled to room temperature, yielding a porous adsorbent powder.
[0055] 5g of 9,10-diphenylanthracene was dissolved in methanol to obtain a 9,10-diphenylanthracene-methanol solution. The porous adsorbent material powder obtained in the above steps was immersed in the 9,10-diphenylanthracene-methanol solution and stirred continuously for 30 min. The stirred mixed suspension was filtered to obtain a precipitate sample, which was then vacuum dried at 100℃ for 2 h. After drying, helium gas was purged until the material cooled to room temperature to obtain a fluorescence-enhanced porous adsorbent material powder.
[0056] Test case
[0057] Test Example 1: Determination of Adsorption Capacity
[0058] Two g of the porous material obtained in Example 1 was loaded into a dynamic adsorption test column (adsorption column inner diameter 4 cm, outer diameter 6 cm, length 15 cm). The dynamic adsorption capacity of the material for krypton was tested at 298.15 K and one standard atmosphere using a mixture of krypton and air (krypton volume concentration of 100 ppm, test flow rate of 10 ml / min). The test results showed that the dynamic adsorption capacity of the material for krypton was approximately 0.13 mmol / kg.
[0059] The porous material obtained in Example 2 was tested in the same manner. The test results showed that the dynamic adsorption capacity of the material in Example 2 for krypton was approximately 0.13 mmol / kg.
[0060] Test Example 2: Determination of Detection Efficiency
[0061] Kr-85 standard radioactive gas was used (Kr-85 activity concentration is 10). 5 Bq / m 3 The detection efficiency of this material for Kr-85 gas was tested using a nitrogen-mixed gas. The novel material was used to completely adsorb 100 Bq of a Kr-85 gas mixture. The adsorbed material was then transferred to a single-photon measurement system to test its emission count. After continuous measurement for 5 minutes, the count rate of the single-photon counting system stabilized at 28 ± 0.7 (cps). Therefore, the detection efficiency of the material obtained in Example 2 for Kr-85 gas is approximately 28%.
[0062] The porous material obtained in Example 1 was tested in the same manner. The test showed that after 5 minutes of continuous measurement, the count rate of the single-photon counting system stabilized at 19 ± 0.6 (cps). Therefore, the detection efficiency of the material obtained in Example 1 for Kr-85 gas is approximately 19%.
[0063] Although this disclosure has been described with reference to specific exemplary embodiments thereof, many different variations, modifications, etc. will become apparent to those skilled in the art.
[0064] By studying the accompanying drawings, the disclosure, and the appended claims, those skilled in the art can understand and implement variations of the disclosed embodiments in the practice of this disclosure.
Claims
1. A porous material comprising a metal-organic framework material, wherein the metal-organic framework material comprises metal ions and organic ligands; in, The metal ion is copper ion (Cu). 2+ ) and cerium ions (Ce) 3+ The organic ligand is 3,6-bis-4-pyridyl-1,2,4,5-tetraazine; At least 80% of the micropores in the porous material have The aperture.
2. The porous material according to claim 1, wherein, The molar ratio of copper ions to cerium ions ranges from 1 to 5.
3. The porous material according to claim 1 or 2, wherein, The BET specific surface area of the porous material is 2185 m². 2 / g.
4. The porous material according to any one of claims 1 to 3, wherein, The porous material further includes a fluorescent material, optionally selected from 9,10-diphenylanthracene.
5. A method for preparing a porous material according to any one of claims 1 to 4, comprising: Step 1: Mix and dissolve hexafluorosilicic acid, copper hydroxide, and cerium hydroxide to obtain a first solution containing CuSiF6 and Ce2(SiF6)3; Step 2: Slowly add the first solution dropwise into 3,6-bis-4-pyridyl-1,2,4,5-tetraazine to obtain the second solution; Step 3: Heat the second solution and continue stirring; Step 4: Slowly add a mixed solution of thiol and methanol dropwise to the second solution and continue stirring to obtain a suspension; as well as Step 5: Filter the suspension, then wash the precipitate and dry it to obtain the metal-organic framework material.
6. The method according to claim 5, wherein, The method further includes: Step 6: Immerse the metal-organic framework material in an organic solution of the fluorescent material.
7. The method according to claim 5 or 6, wherein, In step 1, the molar ratio of copper hydroxide to cerium hydroxide is 1 to 5; and / or In step 3, the second solution is added to 30°C and the solution is continuously stirred for 12 hours; and / or In step 4, the volume ratio of thiol to methanol is 0.1 to 1; and the volume ratio of the second solution to the mixture of thiol and methanol is in the range of 1:100 to 1:50; and / or In step 5, the drying is carried out at 100°C under vacuum for 5 hours.
8. The method according to claim 6, wherein, In step 6, the organic solution of the fluorescent material is a methanol solution of 9,10-diphenylanthracene.
9. Use of the porous material according to any one of claims 1 to 4 and the porous material prepared by the method according to any one of claims 5 to 8 in the adsorption and detection of radioactive krypton gas.